The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/ajcp.12076
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Stress Among Seriously Delinquent Youth: Considering the Consequences of Neighborhood Circumstance

Abstract: Myriad factors have been found to have an impact on delinquent behavior and traumatic stress. This study proposes a model that tests the relationship between common predictors of delinquency (neighborhood condition, antisocial peer socialization, and exposure to violence) with traumatic stress. Serial mediation was used to test the relationships between these predictors and traumatic stress. Results indicate the mediation effect between neighborhood conditions and traumatic stress significantly reduces the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Social disorganization theory provides one framework for understanding the relationship between neighborhood structural disadvantage and adolescent dating violence. Another explanation to the association between concentrated disadvantage and dating violence may be that individuals within areas of disadvantage are at a higher risk for exposure to risk factors for dating violence, including being exposed to community violence, interpersonal violence, and traumatic stress (Benson, Fox, DeMaris, & Van Wyk, ; Black et al., ; Jaggers et al., ; Voith & Brondino, ). In addition, these structural neighborhood characteristics may impede the values and norms of a community: violence may be seen as expected, tolerated or necessary (Berg et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social disorganization theory provides one framework for understanding the relationship between neighborhood structural disadvantage and adolescent dating violence. Another explanation to the association between concentrated disadvantage and dating violence may be that individuals within areas of disadvantage are at a higher risk for exposure to risk factors for dating violence, including being exposed to community violence, interpersonal violence, and traumatic stress (Benson, Fox, DeMaris, & Van Wyk, ; Black et al., ; Jaggers et al., ; Voith & Brondino, ). In addition, these structural neighborhood characteristics may impede the values and norms of a community: violence may be seen as expected, tolerated or necessary (Berg et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, adolescence is an important developmental period to consider the influence of neighborhoods, as youth spend an increasing amount of time in social contexts outside of their home (Leventhal, Depéré, & Brooks‐Gunn, ). Neighborhood structural characteristics (e.g., economic disadvantage) and social processes (e.g., social connection) influence adolescent engagement in risk‐related behaviors, educational outcomes, and physical and mental health outcomes, including traumatic stress (Jaggers, Prattini, & Church, ; Leventhal & Brooks‐Gunn, ; Leventhal et al., ). Structural characteristics of disadvantage, including economic status, residential mobility and family disruption, have consistently been associated with higher levels of violent outcomes in urban youth and adults (Romero, Richards, Harrison, Garbarino, & Mozley, ; Voith & Brondino, ).…”
Section: Neighborhoods and Adolescent Dating Violencementioning
confidence: 99%
“…Another research has shown that teenagers who view their closest friends as deviant are likelier to participate in delinquency (Rokven et al, 2017), increasing their propensity to protest, stone pelting in Kashmir and delinquency in Jammu (Mathur, 2016; Khanna et al, 2020). Neighbourhood, peers and exposure to various conflict-related factors affect children’s mental health (Jaggers et al, 2016). They are owing to low academic performance and a lack of rapport between teachers and adolescents (Suri, 2014; Malla, 2019; Dar & Deb, 2020).…”
Section: Introductionmentioning
confidence: 99%